Monitoring land use and land cover changes in the mountainous cities of Oman using GIS and CA-Markov modelling techniques. (February 2020) - Mansour, Shawky; Al-Belushi, Mohammed; Al-Awadhi, Talal
Highlights: During the last decade, an obvious shift in the urban landscape has taken place in Oman. The mountainous settlements has changed from rural to predominately urban landscape. The integration of GIS techniques with the CA-Markov model successfully simulated spatiotemporal of LULC changes. The urban expansion was initially associated with the increased immigration to urban centres. Urban growth in the mountainous cities of Oman has significantly influenced vegetation cover. Abstract: As a result of the socioeconomic transformation, the rapid urban expansion of cities and towns in the Gulf Cooperation Council (GCC) states has predominately led to tremendous pressure on the limited natural resources and loss of productive lands. Indeed, the spatial patterns of urbanisation and their impacts on mountain resources and environment have received little attention, particularly in Oman. Predicting urban growth in the mountainous cities has the potential to better understand the interaction between the spatial growth patterns and the mountain topography. This study aims to analyse spatiotemporal dynamics of land use/land cover (LULC) (2008–2018) and simulate urban expansion (2008–2038) in Nizwa city, Al Dakhliyah governorate, Oman. Cellular Automata (CA)-Markov and geospatial techniques were utilised to assess and project urban growth and land cover changes. The analysis was based on three maps of LULC at equal intervals derived from satellite imageries: Landsat TM for 1998, 2008 and 2018, along with topographic spatial layers (elevation, aspects, and terrain slopes) derived from the ASTER digital elevation model. In addition, other spatial parameters (population density, proximity to urban centres, and proximity to major roads, ) were incorporated in the simulation process. The findings revealed that the actual LULC change during 2008–2018 was 12, 014 ha of net urban growth (418.5 % change), while the simulated change was expected to be 14, 985 ha by 2028, with a total of 37, 465 ha increase in the built-up area and urban growth by 2038. Although the topographic variability will control LULC changes, the urban expansion overly will occupy the arable land across the valleys along with the flat areas. During the next two decades, the built-up areas will dominant, with a large percentage of vacant land (net loss 12, 813 ha) and vegetation cover (net loss 35 ha) will be gradually converted into residential land use. The output of the simulations in this research could serve not only as spatial guidelines for monitoring future trends of LULC dynamics, but also address the threats and deteriorates of urban sustainability in the Omani mountainous cities. Furthermore, identifying bare soils and vegetation areas that are susceptible to urbanisation is of value for the national strategy of future urban planning in Oman.